Will Work-Life Balance Influence or Strengthen Between Employee Training and Productivity? The Study of a Five-Star Resort in Bali - Efin Shu; Davin Gunawan (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
Human resources Management is very crucial in the hospitality industry due to its nature of being labour-intensive. One factor that determines the company's performance is employee productivity, and it is related to the training provided to the employees and their work-life balance. The preliminary studies show that 52.3% of the employees at the resort did not receive their desired holiday rights. There were also complaints about their poor services. The population used in this research is all full-time employees of the five-star resort Bali, 73 employees. The sampling technique used is saturated sampling by taking all the populations as samples. Data is analyzed with the statistical software PLS SEM 4.0. The results of the study indicate that training influences employee productivity positively, while work-life balance does not influence nor moderate employee productivity positively. Therefore, the five-star resort should increase its training activities to improve employee productivity. Since the influence of training on employee productivity is very small by 7.2%, it is suggested that the resort explores other variables that might influence employee productivity such as work discipline, compensation, and employee motivation.